2011
DOI: 10.1002/cncr.26376
|View full text |Cite
|
Sign up to set email alerts
|

Peak and decline in cancer incidence, mortality, and prevalence at old ages

Abstract: BACKGROUND: Cancer incidence and mortality increase with age through much of adulthood, but earlier work has found that these rates decline among the very elderly. To compare incidence and mortality at the oldest ages, the authors investigated both in the same large population, which comprised 9.5% of the United States in 2000. The authors also report age-specific prevalence among the elderly, which has received little attention. METHODS: Twentythree cancer types were studied in men, and 24 cancer types were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 37 publications
5
88
0
1
Order By: Relevance
“…Interestingly, recent research has revealed that cancer incidence rates after about the age of 75 years tend to flatten and thereafter sharply decrease. Possible explanations for this observation are: cells become senescent losing their proliferative potential; age-dependent remodelling of the immune system leads to an increased number of natural killer cells; decreased exposure to carcinogens; and limitation of angiogenesis due to atherosclerosis (29). This may explain the lower than expected prevalence of malignancies in our study patients, in whom only three new lesions were highly suggestive of malignancy.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, recent research has revealed that cancer incidence rates after about the age of 75 years tend to flatten and thereafter sharply decrease. Possible explanations for this observation are: cells become senescent losing their proliferative potential; age-dependent remodelling of the immune system leads to an increased number of natural killer cells; decreased exposure to carcinogens; and limitation of angiogenesis due to atherosclerosis (29). This may explain the lower than expected prevalence of malignancies in our study patients, in whom only three new lesions were highly suggestive of malignancy.…”
Section: Discussionmentioning
confidence: 62%
“…Time, however, is not an independent factor in carcinogenesis, as it is known that cancer prevalence increases with age, but not in a linear fashion. Studies of cancer prevalence among the elderly (>75 years of age) show that in the age group over 90 the prevalence of cancer is lower than in those before 90 [1178][1179][1180]. More specifically, these authors found prevalence of cancer of 35% in the group of elderly individuals aged 75-79; 20% in those over 90, and 15% among centenarians.…”
Section: Faith Baldwin (1893-1978)mentioning
confidence: 95%
“…(e.g. Harding et al 2011) It is unclear whether my recommendation of an immediate reversion to the pre-1980 radiation safety levels would have enabled the Tokyo Electric Power Company (TEPCO) to control the reactors any better in the crucial first day. I think they would and that is implied in INPO (2011).…”
Section: Radiation Accident Managementmentioning
confidence: 99%